Kajian Aksiologi Dalam Pendidikan - Reski Amalia; Rieka Kartika Aulia Rakhmat; Idawati Idawati (Journal on Education, 2025)
This article will discuss various theories of axiology and their application in various aspects of life, with the aim of providing a deeper understanding of how values shape our views of the world and guide our actions within society. Axiology is a branch of philosophy that studies values in human life, including moral, aesthetic, and other values that determine what is considered good, right, or beautiful. The main focus of axiology is to answer questions about the foundation and nature of values, as well as how we evaluate and establish what is valuable in everyday life. Throughout the history of philosophy, various schools of thought have developed, such as Aristotle’s view, which links values with virtue, and Kant’s view, which emphasizes the importance of universal moral principles in determining right actions. Axiology also involves the study of aesthetics, which examines judgments of beauty in art and nature. As time progresses, axiology has become increasingly relevant in addressing social and technological ethical issues, such as justice, freedom, and moral responsibility in the digital age.